Trafficking for Sexual Exploitation into Southern Thailand - Patcharawalai Wongboonsin (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2007)
Human trafficking has been one of the most challenging problems of nation states across the globe since the 20th century. Thailand has lately turned into a country of origin, destination, and transit for human trafficking. So far, the degree of human trafficking into Thailand is still unknown. Studies on human trafficking into Thailand have been mostly carried out in the Mekong Sub-region. The south of Thailand is an under-researched area, particularly when dealing with trafficking for sexual exploitation. This manuscript provides key findings of the research project entitled Trafficking for Sexual Exploitation into Southern Thailand, under the joint support of the Alliance Française Bangkok and the IRASEC. Carried out during December 2006 - December 2007, the study was expected to fill the gap of research in the problem of trafficking for sexual exploitation in Thailand along a qualitative approach. It was designed towards fact-findings for a better understanding with the most updated information on the problem there. In all, the highlight of the contribution of this study is two folds. First, it enriches literatures on human security from the perspective of people on the move through a qualitative study of human trafficking for sexual exploitation into areas of marginal investigation - southern Thailand. Second, it contributes in terms of policy impact for further strengthening of the collaborative efforts at the national and district levels within Thailand as well as at the regional level.